Mycobacteria Protocols - Parish, Tanya.; Parish, Tanya.; Roberts, David M.; Roberts, David M. (Methods in Molecular Biology,, 2015)
Updated and revised, this thorough volume provides a selection of the newest methods, as well as some of the basic methods required for a mycobacterial research laboratory.  Mycobacteria Protocols, Third Edition guides readers through fractionation and analysis of macromolecules, from nucleic acids to proteins, complex lipids, and metabolites.  Detailed and comprehensive protocols are provided for protein and lipid/glycolipid analysis using well-established methods; these are now complemented by a metabolomics chapter in which the complement of metabolites can be profiled. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.  Authoritative and up-to-date, Mycobacteria Protocols, Third Edition will be a resource both to those working in the field, and to newcomers.